COVID-19 in kidney transplantation-implications for immunosuppression and vaccination - Kodali, Lavanya; Budhiraja, Pooja; Gea-Banacloche, Juan (Frontiers in Medicine, 2022)
COVID-19 pandemic continues to challenge the transplant community, given increased morbidity and mortality associated with the disease and poor response to prevention measures such as vaccination. Transplant recipients have a diminished response to both mRNA and vector-based vaccines compared to dialysis and the general population. The currently available assays to measure response to vaccination includes commercially available antibody assays for anti-Spike Ab, or anti- Receptor Binding Domain Ab. Positive antibody testing on the assays does not always correlate with neutralizing antibodies unless the antibody levels are high. Vaccinations help with boosting polyfunctional CD4+ T cell response, which continues to improve with subsequent booster doses. Ongoing efforts to improve vaccine response by using additional booster doses and heterologous vaccine combinations are underway. There is improved antibody response in moderate responders; however, the ones with poor response to initial vaccination doses, continue to have a poor response to sequential boosters. Factors associated with poor vaccine response include diabetes, older age, specific immunosuppressants such as belatacept, and high dose mycophenolate. In poor responders, a decrease in immunosuppression can increase response to vaccination. COVID infection or vaccination has not been associated with an increased risk of rejection. Pre and Post-exposure monoclonal antibodies are available to provide further protection against COVID infection, especially in poor vaccine responders. However, the efficacy is challenged by the emergence of new viral strains. A recently approved bivalent vaccine offers better protection against the Omicron variant.